2008
DOI: 10.1021/np800049y
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibition of Human Phosphodiesterase-5 by Icariin Derivatives

Abstract: Plant extracts traditionally used for male impotence (Tribulus terrestris, Ferula hermonis, Epimedium breVicornum, Cinnamomum cassia), and the individual compounds cinnamaldehyde, ferutinin, and icariin, were screened against phosphodiesterase-5A1 (PDE5A1) activity. Human recombinant PDE5A1 was used as the enzyme source. Only E. breVicornum extract (80% inhibition at 50 µg/mL) and its active principle icariin (1) (IC 50 5.9 µM) were active. To improve its inhibitory activity, 1 was subjected to various structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 25 publications
15
74
1
Order By: Relevance
“…The result revealed that PDE-5 activity was inhibited by the extracts concentration dependently. This finding is in line with previous reports that medicinal plant extracts can inhibit PDE-5 activity, especially plants rich in flavonoids (Dell'Agli et al 2008;Shin et al 2015;Kotirum et al 2015;Pavan et al 2015). The PDE-5 inhibitory potentials of the studied peels could be linked to their rich flavonoid.…”
Section: Discussionsupporting
confidence: 92%
“…The result revealed that PDE-5 activity was inhibited by the extracts concentration dependently. This finding is in line with previous reports that medicinal plant extracts can inhibit PDE-5 activity, especially plants rich in flavonoids (Dell'Agli et al 2008;Shin et al 2015;Kotirum et al 2015;Pavan et al 2015). The PDE-5 inhibitory potentials of the studied peels could be linked to their rich flavonoid.…”
Section: Discussionsupporting
confidence: 92%
“…9 Icarisid II has also been successfully isolated and assessed its PDE5 inhibitory effect. 11,12 This study investigates the effect of icarisid II on diabetic rats with ED and its potential mechanism via assessment of advanced glycosylation end products (AGEs), autophagy, mTOR and the NO-cGMP pathway.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Recent studies have demonstrated that IcaS possessed a variety of pharmacological activities as a melanogenesis inhibitor, 9) phosphodiesterase-5 inhibitor, 10) and with anti-hepatotoxic, 11) anti-osteoporosis, 12) neurite outgrowth, 13) and lifespan extension activities. 14) We have previously reported that IcaS possessed anticancer activity.…”
mentioning
confidence: 99%